Postoperative pericardial effusion: peculiarities of the development and course - K. S. Kiriakov; V. M. Zakharevich; T. A. Khalilulin; N. Y. Zakharevich; N. N. Abramova; O. A. Pozdnyakov (Вестник трансплантологии и искусственных органов, 2021)
Heart transplantation continues to be the gold standard treatment for end-stage chronic heart failure. As with any cardiac surgery, heart transplantation is associated with postoperative complications. One of the most common complications is postoperative pericardial effusion. Heart recipients have a greater risk of developing pericardial effusion than patients after cardiac surgery on their own heart, due to surgical and immunological features. Severe pericardial effusions negatively affect the postoperative period and may be the cause of life-threatening conditions. Identification of risk factors, prevention, early diagnosis and treatment of this disease can significantly reduce the risks of adverse events in this group of patients. The purpose of this literature review is to analyze the development and course of pericardial effusion in heart recipients in world practice.